The influence of Asset Structure, Capital Structure, Ownership Structure on Financial Performance with Business Risk as Intervening and Good Corporate Governance (GCG) as Moderation (Mining Companies Listed on the Indonesia StockÂ ExchangeÂ (BEI)) - Selfi Yanti; I A Sri Brahmayanti; Tri Ratnawati (International Journal of Economics (IJEC), 2023)
The purpose of this study is to determine the effect of asset structure, Capital Structure, and structure ownership against performance finance and risk business. As intervene and good corporate Governance (GCG)) s as Moderation on company mining Which listed in exchange effect Indonesia in the years 2019–2021. Population study This company mines in the selected coal sector (coal production) in a manner of perceptive sampling and selected 13 coal mining companies with a period of research from 2019 to 2021. Data processing techniques in research use PLS with Outer Model Analysis tests, Inner Model analysis tests, and Hypothesis Testing. The results of this study 1) Asset structure is not influential and significant to Risk business; 2) Asset Structure has no significant effect on financial performance; 3) Capital Structure is not influential and significant to Risk business. 4) Capital Structure has no significant effect on Business risk. 5) Ownership Structure has an effect on financial performance. 6) Structure Ownership has no significant influence on financial performance. 7) Risk Business: No Influence Significant on Financial Performance, 8) With good corporate governance in moderation, risk business has no significant influence on financial performance. 9) Asset Structure is not influential or significant on Financial Performance through Risk Business as Intervening, 10) Capital Structure is not influential or significant on Financial Performance through Risk Business as Intervening, 11) Structure Ownership: No Influence Significant on Financial Performance Through Risk Business as Intervening.